2015
DOI: 10.1038/cddis.2014.525
|View full text |Cite|
|
Sign up to set email alerts
|

MCL-1 and BCL-xL-dependent resistance to the BCL-2 inhibitor ABT-199 can be overcome by preventing PI3K/AKT/mTOR activation in lymphoid malignancies

Abstract: Overexpression of anti-apoptotic BCL-2 family members is a hallmark of many lymphoid malignancies, including chronic lymphocytic leukemia (CLL) and non-Hodgkin lymphoma (NHL) that can be targeted with small molecule inhibitors. ABT-199 is a rationally designed BCL-2 homology (BH)-3 mimetic that specifically binds to BCL-2, but not to MCL-1 and BCL-xL. Although the thrombocytopenia that occurs with navitoclax treatment has not been a problem with ABT-199, clinical trials in CLL could benefit by lowering the ABT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
279
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 308 publications
(317 citation statements)
references
References 45 publications
(75 reference statements)
16
279
2
2
Order By: Relevance
“…Similarly, targeted agents that impact on MCL-1 expression through phosphatidylinositol 3-kinase (PI3K) or mammalian target of rapamycin kinase (mTOR), such as idelalisib 10 or NVP-BEZ235, were also effective. 51 We found that increased BCL-xL expression was inversely correlated with that of miR-377 in ABT-199-resistant DLBCL cell lines and that high BCL-xL/low miR-377 expression conferred resistance to venetoclax in CLL patients. 52 Using a hypomethylating agent, 5-azacytidine restored the response by increasing levels of miR-377 and, as a consequence, decreasing levels of BCL-xL.…”
Section: Resistance Mechanism To Venetoclax In B-cell Lymphoid Malignmentioning
confidence: 77%
See 2 more Smart Citations
“…Similarly, targeted agents that impact on MCL-1 expression through phosphatidylinositol 3-kinase (PI3K) or mammalian target of rapamycin kinase (mTOR), such as idelalisib 10 or NVP-BEZ235, were also effective. 51 We found that increased BCL-xL expression was inversely correlated with that of miR-377 in ABT-199-resistant DLBCL cell lines and that high BCL-xL/low miR-377 expression conferred resistance to venetoclax in CLL patients. 52 Using a hypomethylating agent, 5-azacytidine restored the response by increasing levels of miR-377 and, as a consequence, decreasing levels of BCL-xL.…”
Section: Resistance Mechanism To Venetoclax In B-cell Lymphoid Malignmentioning
confidence: 77%
“…50 Our previous study showed that acquired resistance could be obtained after chronic exposure to venetoclax in DLBCL cell lines, resulting in substantial AKT activation and upregulation of MCL-1 and BCL-xL levels that sequestered BIM (Figure 1). 51 Importantly, genetic suppression of AKT, BCL-xL, or MCL-1 could restore sensitivity to venetoclax. Similarly, targeted agents that impact on MCL-1 expression through phosphatidylinositol 3-kinase (PI3K) or mammalian target of rapamycin kinase (mTOR), such as idelalisib 10 or NVP-BEZ235, were also effective.…”
Section: Resistance Mechanism To Venetoclax In B-cell Lymphoid Malignmentioning
confidence: 99%
See 1 more Smart Citation
“…42,43 Recent studies indicated that BH3-mimetics can be used to treat nonlymphoid cancers but mostly in combination with oestrogen antagonists, proteasome inhibitors, specific PI3K-mTOR inhibitors or chemotherapy. 24,[44][45][46][47][48][49] As previous findings from our laboratory demonstrated that E-cadherin-negative lobular breast cancer depends on p120-catenin-mediated activation of RhoA, Rock and subsequent actomyosin contraction, 26 we anticipate that dual inhibition of these pathways might be successful in E-cadherin-negative cancers that are not driven by oncogenic activation of GFR pathways. Although we do not yet know whether RhoA-Rock signals converge onto the GFR-AKT-FOXO axis in the regulation of anoikis resistance, the fact that FOXO expression had no effect on survival of B-RAF/KRAS-mutated MDA-MB-231 cells seems to be in line with this assumption.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, venetoclax sensitivity is variable between different T-ALL patient samples and the emergence of resistance to venetoclax (11)(12)(13) as well as the occurrence of dose-limiting toxicities (14) provides a rationale for the evaluation of venetoclax as part of a combination therapy.…”
Section: Introductionmentioning
confidence: 99%